Virtual Ascendance: Video Games and the Remaking of Reality - Griffiths, Devin C. (Rowman & Littlefield Publishers, 2013)
From school lunchrooms to the White House press room, video games are an integral part of our popular culture, and the industry behind them touches all aspects of our lives, gamer and non-gamer alike. Business and entertainment, health and medicine, politics and war, social interaction and education, all fall under its influence. Virtual Ascendance tells the story of a formerly fringe enterprise that, when few were paying attention, exploded into a multi-billion dollar industry affecting the very way we live. Griffiths paints a thorough and vivid picture of the video game industry, illuminating the various, and often bizarre, ways it’s changing how we work, play and live. He brings readers along on his own journey of discovery, from the back room of a small Irish pub where members of the second-largest industry enclave meet each month, to a university clinic where the Wii is being used to treat Parkinson’s sufferers — and everywhere in between. Virtual Ascendance is more than just a story about video games, though. It’s the story of an awakening, of a realization that a childhood pastime has exploded into a thriving enterprise — one rooted in entertainment but whose tendrils reach into virtually all aspects of life and society.